11β-Hydroxymedroxyprogesterone - Sharifah Nurfazilah Wan Yusop; Sadia Sultan; Bohari M. Yamin; Syed Adnan Ali Shah; Humera Naz (IUCrData, 2016)
The title compound, C22H32O4, a fungal-transformed metabolite of medroxyprogesterone, comprises one cyclohexanone ring, two cyclohexane rings and one cyclopentane ring fused together. The cyclohexanone ring has a half-chair conformation, while the cyclohexane rings possess chair conformations and the cyclopentane ring has a twisted conformation on the fused C—C bond. In the crystal, molecules are linked by strong O—H...O and also C—H...O hydrogen bonds, creating a two-dimensional network parallel to (10-1).